KONTRIBUSI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM PEMBELAJARAN IPS TERHADAP PENGUASAAN KONSEP SISWA - M. Taufik (PGSD Universitas Negeri Medan, 2018)
The aims of this study is to know how about contribution of STAD type cooperative learning model in IPS Madrasah Ibtidaiyah learning to mastery of student concept. This research uses quasi experimen method, which is done in two class groups, namely: control group and experiment group in fourth grade students of Madrasah Ibtidaiayah Negeri Korong Gadang Kota Padang. Data collection techniques in this study through, test, observation and interviews and documentation. IPS learning with STAD type Cooperative Learning model contributes positively to the improvement of students' concept of mastery .. So based on this research STAD model Cooperative Learning model can be the alternative for teachers in Madrasah Ibtidaiayah or in Elementary School who want the realization of IPS learning objectives as expected. It can be proved by comparing the gain and N-Gain values between the control and experiment classes. Obtain the average gain and N-gain of 1.06 and 0.01 in the control class and 2.38 and 0.02 in the experimental class.Keywords: Leaning Model STAD, IPS, Mastery of Student Consept.